DINAMIKA IMPLEMENTASI PENDEKATAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA - Kusumawardhani, Dwinanda Linchia Levi Heningdyah Nikolas (UNES Law Review, 2023)
Restorative justice has emerged as an alternative approach to the traditional criminal justice system, focusing on the restoration of relationships and addressing the needs of victims, offenders, and communities. This paper explores the concept of restorative justice and its role in achieving substantial justice in the resolution of criminal offenses. By emphasizing dialogue, accountability, and repair, restorative justice seeks to transform the traditional punitive model into a more inclusive and participatory process. The paper examines the key principles and practices of restorative justice, highlighting its potential benefits for both victims and offenders. It explores how restorative justice processes provide opportunities for victims to express their feelings, receive apologies, and actively participate in the decision-making process. For offenders, restorative justice offers a chance to take responsibility for their actions, make amends, and reintegrate into the community. Furthermore, the paper discusses the challenges and limitations of implementing restorative justice within the existing criminal justice system. It acknowledges the need for comprehensive legislative frameworks, trained facilitators, and community support to ensure the successful integration of restorative justice practices. The findings suggest that restorative justice holds promise in fostering healing, rehabilitation, and social reintegration. By prioritizing the needs and voices of victims and offenders, restorative justice promotes a more balanced and humanized approach to justice. Its emphasis on repairing harm and building stronger communities contributes to the overall effectiveness and fairness of the criminal justice system.